A single oral dose of beetroot-based gel does not improve muscle oxygenation parameters, but speeds up handgrip isometric strength recovery in recreational combat sports athletes - Gustavo Vieira de Oliveira; Luiz Diniz do Nascimento; Mônica Volino-Souza; Otávio do Couto Vellozo; Thiago Silveira Alvares (Termedia Publishing House, 2020)
Although the effect of beetroot supplementation on exercise performance has been widely demonstrated to improve the performance of cyclists, runners, and swimmers, its effect on combat sports remains inconclusive. The present study assessed the effect of beetroot-based gel (BG) supplementation on maximal voluntary contraction (MVC), exercise time until fatigue (ETF), muscle O2 saturation (SmO2), and blood volume (tHb) in response to handgrip isotonic exercise (HIE) in recreational combat sport athletes. In a randomized, crossover, double-blind study, 14 combat sports athletes performed three sets of HIE (at 40% MVC) until fatigue after BG or nitrate-depleted gel (PLA) supplementation, in which forearm SmO2 and tHb were continuously monitored using near-infrared spectroscopy. MVC was evaluated at baseline and 20 min after HIE. MVC values were analysed as the change from baseline values (ΔMVC). There was a significant increase accompanied by a large effect size in ΔMVC (p = 0.036, d = 0.94) after HIE in the BG condition compared to PLA. However, there were no changes in SmO2 parameters (p> 0.05), tHb (p> 0.05) or ETF (p = 0.161) throughout the three sets of HIE. Additionally, a trivial to small effect size was observed in near-infrared spectroscopy (NIRS) parameters and ETF (d = ≤ 0.2 to 0.5). Therefore, a single dose of beetroot gel supplementation may be considered as a good nutritional strategy to improve strength recovery in combat sports athletes.